A novel polymerase chain reaction assay to detect Mycoplasma genitalium. Issue 1 (1st February 2003) - Eastick, K; Leeming, J P; Caul, E O; Horner, P J; Millar, M R
Abstract : Aims: To design and validate a polymerase chain reaction (PCR) assay targeting the 16S rRNA gene of Mycoplasma genitalium . Methods: Primers were designed that were complementary to the 16S rRNA gene sequence of M genitalium . After optimisation of the reaction conditions, the PCR was tested against nine M genitalium strains, a dilution series of M genitalium DNA, and a panel of common microorganisms. The PCR was also challenged in parallel with a published assay against 54 urine specimens from men with urethritis. Results: The expected 341 bp product was produced on amplification of material from all M genitalium strains and from none of the other microorganisms tested. The lower limit of detection was 50 genome copies. The new assay detected M genitalium DNA in nine of 54 men with urethritis, in comparison with eight positive specimens detected with the alternative PCR. Conclusions: This novel PCR targeting the M genitalium 16S rRNA gene has been optimised and now provides a sensitive and specific alternative or addition to the available MgPa gene targeting assays.